Addressable graphene encapsulation of wet specimens on a chip for optical, electron, infrared and X-ray based spectromicroscopy studies. Issue 23 (22nd October 2021) - Arble, Christopher; Guo, Hongxuan; Matruglio, Alessia; Gianoncelli, Alessandra; Vaccari, Lisa; Birarda, Giovanni; Kolmakov, Andrei
Abstract : A microchip for spectromicroscopy of biological materials employs a graphene enclosure to separate hydrated samples from a vacuum environment. Co-encapsulated lithographically defined hydrogel microstructures extend the lifetime of the hydrated state. Abstract : Label-free spectromicroscopy methods offer the capability to examine complex cellular phenomena. Electron and X-ray based spectromicroscopy methods, though powerful, have been hard to implement with hydrated objects due to the vacuum incompatibility of the samples and due to the parasitic signals from (or drastic attenuation by) the liquid matrix surrounding the biological object of interest. Similarly, for many techniques that operate at ambient pressure, such as Fourier transform infrared spectromicroscopy (FTIRM), the aqueous environment imposes severe limitations due to the strong absorption of liquid water in the infrared regime. Here we propose a microfabricated multi-compartmental and reusable hydrated sample platform suitable for use with several analytical techniques, which employs the conformal encapsulation of biological specimens by a few layers of atomically thin graphene. Such an electron, X-ray, and infrared transparent, molecularly impermeable and mechanically robust enclosure preserves the hydrated environment around the object for a sufficient time to allow in situ examination of hydrated bio-objects with techniques operating under both ambient and high vacuum conditions. An additional hydration source, provided by hydrogel pads lithographically patterned in the liquid state near/around the specimen and co-encapsulated, has been added to further extend the hydration lifetime. Note that the in-liquid lithographic electron beam-induced gelation procedure allows for addressable capture and immobilization of the biological cells from the solution. Scanning electron microscopy and optical fluorescence microscopy, as well as synchrotron radiation based FTIR and X-ray fluorescence microscopy, have been used to test the applicability of the platform and for its validation with yeast, A549 human carcinoma lung cells and micropatterned gels as biological object phantoms.